DNA database law: a comparative study between Malaysia and Singapore / Che Muhammad Amir Che Lai … [et al.] - Che Lai, Che Muhammad Amir; Shariffuddin, Amir Munzir; Harun Alrashid, Hariz Zikri; Nor Mohamed Arif, Raimizad (2010)
This research is a comparative analysis on the suitability of the DNA Identification Law governing the DNA matters in Malaysia in which special reference of laws in Singapore through its Registration of Criminals Act is made. This study aims at ascertaining the issue of collecting the DNA, removing, issue of privacy as well as the foreign enforcement agency in Malaysia, by drawing comparison with Singapore. This is due to the fact that Malaysia had only recently established the DNA Identification Act whilst in Singapore, DNA matters was governed in the Criminal Law Temporary Provision Act before it was indicated in the Registration of Criminals Act. We have found few loopholes that may be fixed in order to make the newly established Act a succinct and useful one, especially to the society. Thus, this comparative study is important in order to determine any drawback(s) in our Act in comparison with the Singapore's.